Religion, pluralism, and democracy: a natural law approach - Mansueto, Anthony E. (The journal of religion & society, 2008)
This article argues for a democratic theory rooted in natural law. Humanity’s earliest wave of democratization took place in the Axial Era and was intimately bound up with efforts on the part of ordinary people to gain full participate in deliberation regarding fundamental questions of meaning and value. Modern democratic theory, by comparison, tends to exclude deliberation around fundamental questions and focuses debate around themeansto realizing a given end: the modern project of transcending finitude by means of scientific and technological progress. The paper argues for grounding democracy in the shared capacity of all human beings to deliberate around fundamental questions of meaning and value and for understanding democracy as just precisely such a deliberation.